A flame retardant high-strength fire hose and preparation method thereof
Through the five-layer structural design and the combination of functional materials, the flame retardant and mechanical properties of the fire hose are improved, and the shortcomings in strength and flame retardant properties of the existing fire hose are solved, thereby achieving efficient water supply and structural stability at the fire site.
Patent Information
- Application Number
- CN202411269537.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing fire hoses have shortcomings in strength and flame retardant properties, making it difficult to maintain structural integrity and continuously supply water at the fire site.
The five-layer structural design is adopted, including the outer protective layer, the flame retardant layer, the braided layer, the reinforcement layer and the inner liner layer. The flame retardant and mechanical properties of the water belt are improved by surface-modified magnesium hydroxide microtubes covering the flame retardant and the surface-modified beaded silicon carbide nanowires.
The high strength, high toughness and excellent flame retardant properties of the fire hose are achieved, and the structural integrity can be maintained at the fire site for a long time, ensuring the continuous supply of fire extinguishing water.
Smart Images

Figure CN119116466B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fire hoses, and in particular to a flame-retardant high-strength fire hose and a preparation method thereof. Background Art
[0002] In the field of firefighting and rescue, the performance of fire hoses, as key equipment for delivering water sources and pressure, is directly related to the efficiency and safety of fire fighting. An ideal fire hose needs to have both excellent flame retardant properties and high strength characteristics. Good flame retardant properties can prevent the hose from being quickly burned in a high-temperature fire scene, ensure the continuity and stability of water supply, and win precious time for firefighting operations. At the same time, the fire hose must also have sufficient mechanical strength and wear resistance to withstand the impact of high-pressure water flow and the wear of complex rescue environments, ensuring that it can maintain stable performance and structural integrity under harsh conditions. Improving the flame retardancy and strength of fire hoses is of great significance for enhancing the reliability of firefighting equipment, expanding the scope of application, improving fire extinguishing efficiency, and protecting the lives of firefighters. It is an important direction for promoting the advancement of firefighting and rescue technology.
[0003] At present, there have been many attempts in the prior art to improve the flame retardant and mechanical properties of fire hoses, but there are still certain limitations. For example, the publication number CN103438299A discloses a flame retardant fire hose, which improves the fire resistance of the hose by adding hydrophilic substances, but the flame retardant effect is limited, and the hydrophilic substances may have an adverse effect on the mechanical properties of the hose. On the other hand, the Chinese patent with the publication number CN111140708A proposes a strength-enhanced fire hose, which improves the strength of the hose by optimizing the microstructure and material selection, but does not take into account the flame retardant properties, and still faces certain safety hazards in practical applications. In addition, the existing flame retardant and reinforcement methods often adopt different technical routes, lacking a system solution that takes into account both flame retardant and mechanical properties. Therefore, it is urgent to develop a new type of fire hose that can ensure excellent flame retardant properties while having high strength and wear resistance to meet the stringent requirements of fire rescue. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a flame retardant and high-strength fire hose and a preparation method thereof, so as to solve the problem that the current fire hose has insufficient strength and flame retardant performance.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A flame-retardant and high-strength fire hose, which comprises an outer protective layer, a flame-retardant layer, a braided layer, a reinforcement layer and an inner lining layer from the outside to the inside;
[0009] The flame retardant layer is composed of the following raw materials in parts by weight: 3-7 parts of surface modified magnesium hydroxide microtube coated flame retardant, 8-15 parts of thermoplastic elastomer, 5-8 parts of polypropylene, 12-18 parts of polyethylene, 1.0-1.6 parts of Irganox1010 antioxidant, 2-5 parts of ethylene-vinyl acetate copolymer, 0.5-2 parts of nano-montmorillonite and 0.4-1.2 parts of zinc stearate;
[0010] The surface-modified magnesium hydroxide microtube-coated flame retardant is prepared by surface modification of magnesium hydroxide microtube-coated ammonium polyphosphate by maleic anhydride grafted polypropylene;
[0011] The reinforcing layer is composed of the following raw materials in parts by weight: 5-10 parts of surface modified beaded silicon carbide nanowires, 30-45 parts of polyvinyl chloride resin, 12-18 parts of ethylene-vinyl acetate copolymer, 2-5 parts of dioctyl adipate, 1.0-3.0 parts of castor oil, 1.0-1.8 parts of stearic acid, and 0.6-1.2 parts of zinc stearate.
[0012] The surface-modified linked beaded silicon carbide nanowires are prepared by surface-modifying linked beaded silicon carbide nanowires with 3-methacryloxypropyltrimethoxysilane.
[0013] Furthermore, the preparation method of the surface modified magnesium hydroxide microtube coated organic flame retardant is as follows: after 2 to 5 parts of maleic anhydride grafted polypropylene and 100 parts of butyl acetate are evenly mixed by weight, 4 to 10 parts of magnesium hydroxide microtube coated flame retardant are added thereto and stirred for 5 to 10 minutes, and then filtered to obtain solid powder, and then dried completely in a vacuum drying oven at room temperature.
[0014] Furthermore, the preparation method of the magnesium hydroxide microtube coated flame retardant is as follows: surface modification of the magnesium hydroxide microtube: by weight, 3 to 8 parts of ammonium polyphosphate, 1.0 to 2.0 parts of sodium dodecyl sulfate and 50 parts of deionized water are mixed evenly, the pH of the solution is adjusted to 5 with 2% dilute hydrochloric acid, and then 4 to 9 parts of magnesium hydroxide microtubes are added, ultrasonic treatment is performed for 15 to 25 minutes, and then the mixture is transferred to a hydrothermal reactor, reacted at 100 to 120° C. for 6 to 10 hours, cooled to room temperature, centrifuged to obtain a solid powder, washed with deionized water 3 times, and finally vacuum dried at 60° C. for 10 to 18 hours to obtain the magnesium hydroxide microtube coated flame retardant.
[0015] Furthermore, the preparation method of the magnesium hydroxide microtubes is as follows: by weight, 5 to 10 parts of magnesium chloride are dissolved in 1000 parts of deionized water, stirred until completely dissolved, 2 mol / L NaOH aqueous solution is slowly added dropwise until the pH reaches 10 to 11, the mixture is transferred to a hydrothermal reactor, reacted at 170 to 120° C. for 10 to 15 hours, cooled to room temperature, centrifuged, washed with deionized water and ethanol three times respectively, and finally vacuum dried at 55 to 65° C. for 10 to 15 hours to obtain magnesium hydroxide microtubes.
[0016] The purpose of the present invention using surface-modified magnesium hydroxide microtubes coated with organic flame retardants is mainly to increase the flame retardant performance and strength of fire hoses. First, the improvement of flame retardant performance is mainly due to the use of surface-modified magnesium hydroxide microtubes coated with flame retardants in the flame retardant layer. Magnesium hydroxide microtubes are inorganic materials and have excellent flame retardancy. Their tubular structure can form a stable barrier layer when heated to delay the spread of heat and combustible gas. By coating ammonium polyphosphate flame retardant on the surface of magnesium hydroxide microtubes, the flame retardant efficiency of the material can be further improved. Ammonium polyphosphate releases nitrogen and water vapor when decomposed by heat to dilute the concentration of combustible gas. At the same time, the generated phosphoric acid and metaphosphoric acid and other substances can also catalyze the carbonization of the substrate to form a dense barrier layer. In addition, the magnesium hydroxide microtube coated flame retardant is surface-modified by maleic anhydride grafted polypropylene, which can significantly improve its compatibility with the matrix resin, promote the uniform dispersion of the flame retardant in the material, and give full play to the flame retardant effect. In addition to the flame retardant, the flame retardant layer is compounded with thermoplastic elastomers, polypropylene, polyethylene and other polymer materials, which can give the material excellent mechanical properties. Thermoplastic elastomers have the high elasticity of rubber and the processability of plastics, and are ideal for improving the toughness of materials. Polypropylene and polyethylene can provide higher strength and modulus. By compounding them in appropriate proportions, a flame retardant material with both high strength and high toughness can be obtained. In addition, the addition of nano-montmorillonite can not only further improve the flame retardancy, but also strengthen the matrix through its flaky structure, playing a role similar to nano-enhancement. In summary, the present invention starts from multiple angles such as molecular structure design, material compounding, and coating structure construction, and obtains a new type of fire hose with excellent flame retardancy and mechanical properties through the synthesis of surface-modified nano flame retardants, the optimization of flame retardant toughening systems, and reasonable interlayer matching. This high-performance hose can maintain structural integrity for a long time at the fire scene, ensure the continuous supply of water for fire fighting, and provide a new solution for improving fire fighting efficiency and ensuring fire safety.
[0017] Furthermore, the preparation method of the surface-modified beaded silicon carbide nanowires is as follows: by weight, 30 to 50 parts of beaded silicon carbide nanowires and 500 parts of anhydrous ethanol are added to a beaker, and then 4 to 8 parts of 3-methacryloxypropyltrimethoxysilane are added, followed by stirring at room temperature for 60 to 90 minutes. After stirring, the solid powder is collected by filtering, and the surface-modified beaded silicon carbide nanowires are obtained after being completely dried in a vacuum drying oven at room temperature.
[0018] Furthermore, the preparation method of the beaded silicon carbide nanowires is as follows: after uniformly mixing 20 to 40 parts of polycarbosilane, 1 to 3 parts of ferrocene and 100 parts of xylene, by weight, the mixture is placed in a vacuum drying oven and dried for 12 to 24 hours to obtain a solid precursor, and then the solid precursor is ground into powder and placed in a ceramic ark, placed in an atmosphere tube furnace, heated to 1200 to 1400°C under an argon atmosphere, kept warm for 2 to 4 hours, and then cooled to room temperature to obtain beaded silicon carbide nanowires.
[0019] The present invention adopts surface-modified beaded silicon carbide nanowires, which are designed to enhance the mechanical properties of fire hoses. Beaded silicon carbide nanowires are a new type of nano-reinforced material with excellent mechanical properties and high temperature resistance. Its unique beaded structure can effectively increase the interface bonding between the nanowires and the matrix, thereby significantly improving the strength and toughness of the material. In addition, silicon carbide itself has the characteristics of high strength, high modulus, wear resistance, etc., so the beaded silicon carbide nanowires are ideal mechanical reinforcement fillers. In order to further improve the compatibility of the beaded silicon carbide nanowires with the polymer matrix, the present invention uses 3-methacryloxypropyltrimethoxysilane to perform surface modification treatment on them. One end of the silane coupling agent contains a silane group that reacts with the surface of the inorganic filler, and the other end contains a functional group that can chemically bond or physically entangle with the organic polymer. Through silane modification, organic groups can be introduced on the surface of the inorganic filler to play a role in volume expansion, thereby significantly improving the dispersibility of the filler and the interfacial adhesion with the matrix, and ultimately achieving the purpose of improving the mechanical properties of the material. In the reinforcement layer, in addition to the surface-modified beaded silicon carbide nanowires, polyvinyl chloride resin and ethylene-vinyl acetate copolymer are also used as matrix materials. Polyvinyl chloride resin has excellent flame retardancy and weather resistance, while ethylene-vinyl acetate copolymer gives the material good flexibility. The two are compounded to obtain a composite material with high strength, high toughness and flame retardancy. In addition, dioctyl adipate as a plasticizer can improve the flexibility and processing properties of the material; castor oil, stearic acid and zinc stearate are used as lubricants and thermal stabilizers to improve the fluidity and thermal stability of the material. There is an obvious synergistic effect between the components. Surface-modified beaded silicon carbide nanowires as nano-reinforced fillers can significantly improve the mechanical properties of the matrix; while polyvinyl chloride and ethylene-vinyl acetate copolymer matrices provide a good dispersion matrix and stress transfer channel for the nanowires. The addition of plasticizers and lubricants can improve the dispersibility of nanowires and their compatibility with the matrix, thereby giving full play to their reinforcing effect. In summary, the present invention ingeniously utilizes the synergistic reinforcement effect between surface-modified beaded silicon carbide nanowires and the polymer matrix, and obtains a fire hose reinforcement layer material with both high strength and high toughness through surface modification of nanofillers, reasonable selection of matrix resins, and optimization of compound components. This high-performance hose can maintain excellent mechanical properties and dimensional stability at the fire scene, thereby providing solid and reliable equipment support for firefighting and rescue.
[0020] Furthermore, the outer protective layer is prepared from the following components in parts by weight: 15 to 25 parts of stainless steel powder, 4 to 9 parts of aluminum oxide powder, 3 to 8 parts of basalt fiber roving, 30 to 60 parts of ethylene-vinyl acetate copolymer, 10 to 18 parts of polypropylene and 2 to 5 parts of fluorescent powder.
[0021] Furthermore, the thickness of the outer protective layer is 0.8-1.2 mm; the thickness of the flame retardant layer is 1.5-2.0 mm; the thickness of the braided layer is 1.0-1.5 mm; the thickness of the reinforcement layer is 1.8-2.5 mm; and the thickness of the lining layer is 1.2-1.8 mm.
[0022] The present invention adopts a design of compounding a polymer matrix with a plurality of inorganic fillers, which is mainly used to enhance the wear resistance and mechanical properties of the outer protective layer of the fire hose. The outer protective layer is the outermost structural layer of the fire hose, which is directly exposed to the harsh use environment and needs to have excellent wear resistance and mechanical strength to resist external forces such as wear and impact. The present invention cleverly introduces inorganic fillers such as stainless steel powder, aluminum oxide powder and basalt fiber roving into ethylene-vinyl acetate copolymer and polypropylene matrix, and achieves performance improvement through multi-component synergistic enhancement. Stainless steel powder has high hardness and high strength and is an ideal wear-resistant filler. Evenly dispersing it in the polymer matrix can significantly improve the wear resistance and impact resistance of the material. Aluminum oxide powder is also a ceramic filler with relatively high hardness, which, like stainless steel powder, can play a role in wear resistance enhancement. In addition, aluminum oxide also has excellent insulation and thermal conductivity, which helps to improve the thermal stability of the material. Basalt fiber roving plays a role in toughening and strengthening. Basalt fiber has the characteristics of high strength, high modulus, and high temperature resistance. When it is introduced into the polymer matrix in the form of roving, it can form a network-like reinforcement structure and improve the toughness and impact resistance of the material. Ethylene-vinyl acetate copolymer and polypropylene are two commonly used polymer matrix materials. Ethylene-vinyl acetate copolymer has excellent flexibility, weather resistance and chemical resistance, while polypropylene has high strength and rigidity. The two are compounded in an appropriate proportion to obtain a matrix material with both high strength and high toughness. There is an obvious synergistic reinforcement effect between inorganic fillers and organic matrices. The filler particles are dispersed in the matrix, which can hinder the propagation of cracks when subjected to force, while the fiber filler plays a bridging and toughening role, jointly improving the strength and toughness of the material. At the same time, the interfacial interaction between the filler and the matrix can effectively transfer stress, so that the mechanical properties of the material are improved as a whole. In addition, fluorescent powder is added to the outer protective layer, so that the water hose has the tracking function at night and in low light environments, which is convenient for firefighters to identify and track the water hose, and improves the safety and convenience of use. In summary, the invention achieves a significant improvement in the wear resistance and mechanical properties of the outer protective layer of the fire hose by rationally compounding stainless steel powder, aluminum oxide powder and basalt fiber roving, and combining them with ethylene-vinyl acetate copolymer and polypropylene matrix. Combined with the fluorescent tracing function, the resulting hose can meet the use requirements of harsh firefighting environments.
[0023] In terms of overall structural design, the present invention adopts a five-layer structure, and the thickness of each layer is reasonably designed and matched, which ensures the performance of the hose while taking into account the need for lightweight. The design of the outer protective layer and the flame retardant layer gives the hose excellent wear resistance and flame retardancy; the braided layer and the reinforcement layer guarantee the mechanical properties of the hose; the inner lining layer is made of hydrolysis-resistant and aging-resistant materials, which can ensure the smoothness of the inner wall of the hose and reduce water transmission resistance. This multi-layer composite structure design can give full play to the role of each functional layer and obtain a high-strength flame-retardant fire hose with excellent performance.
[0024] The present invention also provides a method for preparing a flame-retardant high-strength fire hose, comprising the following steps:
[0025] S1. Preparation of inner lining layer: heating EPDM rubber to 170-200°C to obtain a colloid, feeding it into an extruder, extruding it on a cylindrical mold, and obtaining a cylindrical lining layer after cooling.
[0026] S2. Preparation of a reinforcing layer: uniformly mix the components for preparing the reinforcing layer according to their weight proportions and add them into a furnace for smelting at a smelting temperature of 180-220° C. The smelted colloid is sent to a twin-screw extruder for extrusion, and after cooling, a reinforcing layer is obtained outside the inner lining layer.
[0027] S3. Prepare the braided layer: apply adhesive on the reinforcing layer, and use nylon thread and fine steel wire to interlace and pull to weave the warp and weft to form a braided layer.
[0028] S4, preparing a flame retardant layer: the components for preparing the flame retardant layer are mixed uniformly according to weight proportions and added into a furnace for melting at a melting temperature of 180-220° C., and then extruded through an extruder to form a flame retardant layer wrapping the strong woven layer.
[0029] S5. Preparation of an outer protective layer: The components of the outer protective layer of the fire hose are uniformly mixed according to weight proportions, and then stirred at 150-200° C. to obtain a colloid, which is then extruded onto the flame retardant layer to obtain the outer protective layer.
[0030] S6. Heat treatment: The prepared fire hose is heat treated at 80-90°C for 2-3h to release the internal stress, and then the mold is taken out to complete the preparation of the flame-retardant high-strength fire hose.
[0031] Furthermore, the twin-screw extruder in step S2 has a screw L / D ratio of 36:1 and a rotation speed of 100-150 rpm.
[0032] Furthermore, in step S3, the braiding density of the braided layer is 16-20 strands / inch, and the braiding angle is 50-55°.
[0033] Furthermore, the parameters of the extruder in step S4 are set as follows: the temperature of the feed section is 165-175°C; the temperature of the compression section is 175-185°C; the temperature of the metering section is 185-195°C; and the head temperature is 195-205°C.
[0034] The present invention adopts a five-layer composite structure and a design of specific process parameters, which is mainly used to prepare a fire hose with high strength, high toughness and excellent flame retardancy. The present invention prepares a five-layer structure fire hose composed of an inner lining layer, a reinforcement layer, a braided layer, a flame retardant layer and an outer protective layer in sequence through multi-step extrusion, braiding and heat treatment processes from the inside to the outside. Each layer adopts a specially designed material formula and process parameters to achieve the optimization and matching of the performance between different layers. The inner lining layer is prepared by high-temperature melt extrusion of EPDM rubber to obtain an inner layer structure with a smooth surface and good flexibility, which is conducive to reducing water flow resistance and improving water delivery efficiency. The reinforcement layer is the main mechanical bearing layer of the water hose. The polyvinyl chloride / ethylene-vinyl acetate copolymer composite material reinforced with surface-modified silicon carbide nanowires is prepared by melt extrusion. The uniform dispersion and surface modification of the nanowires can significantly improve the interfacial adhesion, thereby effectively improving the mechanical properties of the material. The braided layer is made of nylon wire and fine steel wire interlaced braiding. Reasonable weaving angle and density can provide radial restraint while giving the hose higher flexibility, so that it can adapt to complex terrain and harsh use environment. The flame retardant layer and the outer protective layer are respectively prepared by polymer matrix materials filled with flame retardants and are formed by extrusion or extrusion. The synergistic effect between the flame retardant and the matrix can significantly improve the flame retardancy and fire resistance of the hose. The various inorganic fillers added to the outer protective layer give the hose excellent wear resistance and mechanical strength. In terms of preparation process, by reasonably designing parameters such as the screw speed and L / D ratio of the extruder, the mold temperature and the cooling method, an extruded material with good molecular orientation and excellent mechanical properties can be obtained. The introduction of the heat treatment process helps to release the residual stress formed inside the material during the preparation process and improve the dimensional stability and service life of the hose. In general, the design of the five-layer composite structure and the optimization of the preparation process enable the fire hose obtained by the present invention to achieve a comprehensive balance in terms of flame retardancy, mechanical properties, wear resistance and ease of use, and can meet the performance requirements of the hose in harsh firefighting environments. The inner lining layer, reinforcement layer, braided layer, flame retardant layer and outer protective layer each have their own functions and work together to ensure the excellent performance of the hose in terms of water delivery, pressure resistance, and wear resistance. At the same time, the multi-layer composite structure also improves the safety redundancy of the hose. Even if it is partially damaged under extreme conditions, it can continue to maintain its overall performance, thus providing more reliable equipment support for firefighting applications.
[0035] (3) Beneficial technical effects
[0036] The present invention is a high-performance fire hose, which adopts a five-layer composite structure design and a compound of multiple functional materials, and achieves comprehensive improvement in flame retardancy, mechanical properties, wear resistance and ease of use, and has significant advantages over traditional fire hoses.
[0037] 1. In terms of flame retardancy, the present invention uses a composite material of surface-modified magnesium hydroxide microtubes coated with ammonium polyphosphate flame retardant in the flame retardant layer. The magnesium hydroxide microtubes themselves have excellent flame retardancy, and the flame retardant efficiency of the material and its compatibility with the substrate can be further improved by surface coating with flame retardant and maleic anhydride grafting treatment. When heated, the magnesium hydroxide microtubes can form a stable barrier layer, and the phosphoric acid substances produced by the decomposition of ammonium polyphosphate can also catalyze the carbonization of the substrate. The synergistic effect of the two gives the water hose a more excellent flame retardant performance.
[0038] 2. In terms of mechanical properties, the present invention adopts a multi-component synergistic reinforcement strategy, introduces surface-modified beaded silicon carbide nanowires into the reinforcement layer, and compounded with polyvinyl chloride and ethylene-vinyl acetate copolymer matrix, and rationally selects plasticizers and lubricants, and finally obtains a composite material with both high strength and high toughness. After being modified by silane coupling agent, the beaded silicon carbide nanowires have a higher interfacial adhesion with the polymer matrix, and can give full play to its reinforcing effect. The braided layer is made of nylon wire and fine steel wire interlaced, and the reasonable braiding angle and density design further ensure the mechanical strength and flexibility of the hose.
[0039] 3. The improvement of wear resistance is mainly due to the reasonable compounding of various inorganic fillers in the outer protective layer. Stainless steel powder and aluminum oxide powder are both high-hardness wear-resistant fillers. Evenly dispersed in the polymer matrix, they can significantly improve the wear resistance and impact resistance of the material. Basalt fiber roving plays a role in toughening and strengthening, forming a network structure with the polymer matrix, improving the toughness and impact resistance of the material. There is an obvious synergistic enhancement effect between the multiple components, which together give the water hose excellent wear resistance.
[0040] 4. The present invention also fully considers the actual use needs of the fire hose. The inner lining layer is made of EPDM rubber material that is resistant to hydrolysis and aging and is extruded at high temperature to obtain an inner layer structure with a smooth surface and good flexibility, which is conducive to reducing water transport resistance and improving water transport efficiency. Fluorescent powder is added to the outer protective layer to give the hose a nighttime tracing function, which is convenient for firefighters to identify and track, greatly improving the convenience and safety of the hose.
[0041] 5. The present invention achieves synergistic enhancement among components in functional layers such as the flame retardant layer, the reinforcement layer and the outer protective layer through reasonable material design, structural design and preparation process optimization, and finally obtains a new high-performance fire hose that is significantly superior to traditional hoses in terms of flame retardancy, mechanical properties, wear resistance and ease of use. This high-performance hose can maintain excellent comprehensive performance under extreme conditions such as fires, and can continue to function even if it is partially damaged, thereby providing safer and more reliable equipment support for firefighting and rescue operations, which is of great significance to improving firefighting efficiency and reducing the risk of casualties among firefighters, and shows broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the SEM scanning electron microscope morphology of the magnesium hydroxide microtube prepared in Example 1 of the present invention.
[0043] Figure 2 This is the SEM scanning electron microscope morphology of the surface-modified magnesium hydroxide microtubes coated with ammonium polyphosphate flame retardant prepared in Example 1 of the present invention.
[0044] Figure 3 This is the XRD phase analysis diagram of the magnesium hydroxide microtubes prepared in Example 1 of the present invention and the surface-modified magnesium hydroxide microtubes coated with ammonium polyphosphate flame retardant.
[0045] Figure 4 This is the SEM scanning electron microscope morphology of the surface-modified beaded silicon carbide nanowires prepared in Example 1 of the present invention.
[0046] Figure 5 This is the XRD phase analysis diagram of the surface-modified beaded silicon carbide nanowires prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0048] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0049] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0050]
[0051] Example 1
[0052] A flame-retardant and high-strength fire hose, which comprises an outer protective layer, a flame-retardant layer, a braided layer, a reinforcement layer and an inner lining layer from the outside to the inside;
[0053] The flame retardant layer is composed of the following raw materials in parts by weight: 3 parts of surface modified magnesium hydroxide microtube coated flame retardant, 8 parts of thermoplastic elastomer, 5 parts of polypropylene, 12 parts of polyethylene, 1.0 part of Irganox 1010 antioxidant, 2 parts of ethylene-vinyl acetate copolymer, 0.5 parts of nano-montmorillonite and 0.4 parts of zinc stearate;
[0054] The surface-modified magnesium hydroxide microtube-coated flame retardant is prepared by surface modification of magnesium hydroxide microtube-coated ammonium polyphosphate and maleic anhydride grafted polypropylene.
[0055] The reinforcing layer is composed of the following raw materials in parts by weight: 5 parts of surface modified beaded silicon carbide nanowires, 30 parts of polyvinyl chloride resin, 12 parts of ethylene-vinyl acetate copolymer, 2 parts of dioctyl adipate, 1.0 part of castor oil, 1.0 part of stearic acid, and 0.6 parts of zinc stearate.
[0056] The surface-modified linked beaded silicon carbide nanowires are prepared by surface-modifying the linked beaded silicon carbide nanowires with 3-methacryloxypropyltrimethoxysilane.
[0057] The preparation method of the surface modified magnesium hydroxide microtube coated organic flame retardant is as follows: by weight, 5 parts of magnesium chloride are dissolved in 1000 parts of deionized water, stirred until completely dissolved, 2 mol / L NaOH aqueous solution is slowly added dropwise until the pH reaches 10, the mixture is transferred to a hydrothermal reactor, reacted at 170°C for 10 hours, cooled to room temperature, centrifuged, washed with deionized water and ethanol 3 times respectively, and finally vacuum dried at 55°C for 10 hours to obtain magnesium hydroxide microtubes. 3 parts of ammonium polyphosphate, 1.0 part of sodium dodecyl sulfate and 50 parts of deionized water are mixed evenly, the solution is adjusted to pH 5 with 2% dilute hydrochloric acid, and then 4 parts of magnesium hydroxide microtubes are added, ultrasonically treated for 15 minutes, and then the mixture is transferred to a hydrothermal reactor, reacted at 100°C for 6 hours, cooled to room temperature, centrifuged to obtain solid powder, washed with deionized water 3 times, and finally vacuum dried at 60°C for 10 hours to obtain magnesium hydroxide microtube coated flame retardant. After 2 parts of maleic anhydride grafted polypropylene and 100 parts of butyl acetate are evenly mixed, 4 parts of magnesium hydroxide microtube coated flame retardant are added thereto and stirred for 5 minutes, and then filtered to remove the solid powder, which is then completely dried in a vacuum drying oven at room temperature.
[0058] The preparation method of surface-modified beaded silicon carbide nanowires is as follows: after 20 parts of polycarbosilane, 1 part of ferrocene and 100 parts of xylene are mixed evenly by weight, the mixture is placed in a vacuum drying oven and dried for 12 hours to obtain a solid precursor, the solid precursor is then ground into powder and placed in a ceramic ark, placed in an atmosphere tube furnace, heated to 1200°C under an argon atmosphere, kept warm for 2 hours, and then cooled to room temperature to obtain beaded silicon carbide nanowires. 30 parts of beaded silicon carbide nanowires and 500 parts of anhydrous ethanol are added to a beaker, and then 4 parts of 3-methacryloxypropyltrimethoxysilane are added, followed by stirring at room temperature for 60 minutes, and after stirring, the solid powder is collected by filtration, and dried completely in a vacuum drying oven at room temperature to obtain surface-modified beaded silicon carbide nanowires.
[0059] The outer protective layer is prepared from the following components in parts by weight: 15 parts of stainless steel powder, 4 parts of aluminum oxide powder, 3 parts of basalt fiber roving, 30 parts of ethylene-vinyl acetate copolymer, 10 parts of polypropylene and 2 parts of fluorescent powder.
[0060] The thickness of the outer protective layer is 0.8 mm; the thickness of the flame retardant layer is 1.5 mm; the thickness of the braided layer is 1.0 mm; the thickness of the reinforcement layer is 1.8 mm; and the thickness of the inner lining layer is 1.2 mm.
[0061] This embodiment also provides a method for preparing a highly wear-resistant UV matte coating, comprising the following steps:
[0062] S1. Preparation of inner lining layer: heating EPDM rubber to 170° C. to obtain a colloid, feeding it into an extruder, extruding it on a cylindrical mold, and obtaining a cylindrical inner lining layer after cooling.
[0063] S2. Preparation of a reinforcing layer: The components for preparing the reinforcing layer are mixed uniformly according to their weight proportions and then added into a furnace for smelting at a smelting temperature of 180° C. The smelted colloid is sent to a twin-screw extruder for extrusion. After cooling, a reinforcing layer is obtained outside the lining layer. The twin-screw extruder has a screw L / D ratio of 36:1 and a rotation speed of 100 rpm.
[0064] S3. Prepare the braided layer: apply adhesive on the reinforcement layer, and use nylon wire and fine steel wire to interlace and pull to weave the warp and weft to form a braided layer. The braiding density of the braided layer is 16 strands / inch, and the braiding angle is 50°.
[0065] S4, preparation of flame retardant layer: the components for preparing the flame retardant layer are mixed uniformly according to weight proportions and added into a furnace for melting at a melting temperature of 180°C, and then extruded through an extruder to form a flame retardant layer wrapped around the strong braided layer. The parameters of the extruder are set as follows: the feeding section temperature is 165°C, the compression section temperature is 175°C, the metering section temperature is 185°C, and the die head temperature is 195°C.
[0066] S5. Preparation of an outer protective layer: The components of the outer protective layer of the fire hose are uniformly mixed according to weight proportions, and then stirred at 150° C. to obtain a colloid, which is then extruded onto the flame retardant layer to obtain the outer protective layer.
[0067] S6. Heat treatment: The prepared fire hose is heat treated at 80°C for 2h to release the internal stress, and then the mold is taken out to complete the preparation of the flame-retardant high-strength fire hose.
[0068] Figure 1 The SEM scanning electron microscope morphology shows the successfully prepared magnesium hydroxide microtube structure, proving that the method of the present invention can effectively synthesize magnesium hydroxide materials with tubular morphology. Figure 2 The SEM scanning electron microscope morphology reveals the morphological characteristics of the surface-modified magnesium hydroxide microtubes successfully coated with ammonium polyphosphate flame retardant, proving the effectiveness of the surface modification and coating process of the present invention. Figure 3 The XRD phase analysis diagram simultaneously presents the crystal structure characteristics of magnesium hydroxide microtubes and surface-modified magnesium hydroxide microtubes coated with ammonium polyphosphate flame retardant, proving that the material maintains the expected crystal phase composition during the modification and coating process, and shows new characteristic peaks, indicating the successful introduction of ammonium polyphosphate. Figure 4 The SEM scanning electron microscope morphology shows the unique morphology of the surface-modified beaded silicon carbide nanowires, proving that the present invention can successfully prepare nanoscale silicon carbide materials with specific morphology. Figure 5 The XRD phase analysis diagram confirmed the crystal structure of the surface-modified beaded silicon carbide nanowires, proving that the prepared material is indeed silicon carbide. These images and analysis results jointly confirm the effectiveness and innovation of the present invention in preparing various functional nanomaterials, demonstrating the precise control capability from micron to nanometer scale, as well as the process level of successfully achieving surface modification and composite material preparation.
[0069] Example 2
[0070] A flame-retardant and high-strength fire hose, which comprises an outer protective layer, a flame-retardant layer, a braided layer, a reinforcement layer and an inner lining layer from the outside to the inside;
[0071] The flame retardant layer is composed of the following raw materials in parts by weight: 4 parts of surface modified magnesium hydroxide microtube coated flame retardant, 10 parts of thermoplastic elastomer, 6 parts of polypropylene, 14 parts of polyethylene, 1.2 parts of Irganox 1010 antioxidant, 3 parts of ethylene-vinyl acetate copolymer, 1.0 part of nano-montmorillonite and 0.6 parts of zinc stearate;
[0072] The surface-modified magnesium hydroxide microtube-coated flame retardant is prepared by surface modification of magnesium hydroxide microtube-coated ammonium polyphosphate and maleic anhydride grafted polypropylene.
[0073] The reinforcing layer is composed of the following raw materials in parts by weight: 7 parts of surface modified beaded silicon carbide nanowires, 35 parts of polyvinyl chloride resin, 14 parts of ethylene-vinyl acetate copolymer, 3 parts of dioctyl adipate, 1.6 parts of castor oil, 1.2 parts of stearic acid, and 0.8 parts of zinc stearate.
[0074] The surface-modified linked beaded silicon carbide nanowires are prepared by surface-modifying the linked beaded silicon carbide nanowires with 3-methacryloxypropyltrimethoxysilane.
[0075] The preparation method of the surface modified magnesium hydroxide microtube coated organic flame retardant is as follows: by weight, 7 parts of magnesium chloride are dissolved in 1000 parts of deionized water, stirred until completely dissolved, 2 mol / L NaOH aqueous solution is slowly added dropwise until the pH reaches 10, the mixture is transferred to a hydrothermal reactor, reacted at 135°C for 12 hours, cooled to room temperature, centrifuged, washed with deionized water and ethanol 3 times, and finally vacuum dried at 58°C for 12 hours to obtain magnesium hydroxide microtubes. 5 parts of ammonium polyphosphate, 1.3 parts of sodium dodecyl sulfate and 50 parts of deionized water are mixed evenly, the solution is adjusted to pH 5 with 2% dilute hydrochloric acid, and then 6 parts of magnesium hydroxide microtubes are added, ultrasonically treated for 18 minutes, and then the mixture is transferred to a hydrothermal reactor, reacted at 106°C for 7 hours, cooled to room temperature, centrifuged to obtain solid powder, washed with deionized water 3 times, and finally vacuum dried at 60°C for 12 hours to obtain magnesium hydroxide microtube coated flame retardant. After 3 parts of maleic anhydride grafted polypropylene and 100 parts of butyl acetate are evenly mixed, 6 parts of magnesium hydroxide microtube coated flame retardant are added thereto and stirred for 7 minutes, and then filtered to remove the solid powder, which is then completely dried in a vacuum drying oven at room temperature.
[0076] The preparation method of surface-modified beaded silicon carbide nanowires is as follows: 26 parts of polycarbosilane, 2 parts of ferrocene and 100 parts of xylene are mixed evenly by weight, and then placed in a vacuum drying oven, dried for 16 hours to obtain a solid precursor, and then the solid precursor is ground into powder and placed in a ceramic ark, placed in an atmosphere tube furnace, heated to 1260°C under an argon atmosphere, kept warm for 3 hours, and then cooled to room temperature to obtain beaded silicon carbide nanowires. 36 parts of beaded silicon carbide nanowires and 500 parts of anhydrous ethanol are added to a beaker, and then 5 parts of 3-methacryloxypropyltrimethoxysilane are added, followed by stirring at room temperature for 69 minutes. After stirring, the solid powder is collected by filtration, and dried completely in a vacuum drying oven at room temperature to obtain surface-modified beaded silicon carbide nanowires.
[0077] The outer protective layer is prepared from the following components in parts by weight: 18 parts of stainless steel powder, 6 parts of aluminum oxide powder, 5 parts of basalt fiber roving, 39 parts of ethylene-vinyl acetate copolymer, 12 parts of polypropylene and 3 parts of fluorescent powder.
[0078] The thickness of the outer protective layer is 0.9 mm; the thickness of the flame retardant layer is 1.7 mm; the thickness of the braided layer is 1.2 mm; the thickness of the reinforcement layer is 2.0 mm; and the thickness of the inner lining layer is 1.4 mm.
[0079] The present invention also provides a method for preparing a highly wear-resistant UV matte coating, comprising the following steps:
[0080] S1. Preparation of inner lining layer: heating EPDM rubber to 179° C. to obtain a colloid, feeding it into an extruder, extruding it on a cylindrical mold, and obtaining a cylindrical inner lining layer after cooling.
[0081] S2. Preparation of a reinforcing layer: The components for preparing the reinforcing layer are mixed uniformly according to their weight proportions and then added into a furnace for smelting at a smelting temperature of 192° C. The smelted colloid is sent to a twin-screw extruder for extrusion. After cooling, a reinforcing layer is obtained outside the lining layer. The twin-screw extruder has a screw L / D ratio of 36:1 and a rotation speed of 115 rpm.
[0082] S3. Prepare the braided layer: apply adhesive on the reinforcement layer, and use nylon wire and fine steel wire to interlace and pull to weave the warp and weft to form a braided layer. The braiding density of the braided layer is 17 strands / inch, and the braiding angle is 52°.
[0083] S4, preparation of flame retardant layer: the components for preparing the flame retardant layer are mixed uniformly according to weight proportions and added into a furnace for melting at a melting temperature of 192°C, and then extruded through an extruder to form a flame retardant layer wrapped around the strong braided layer. The parameters of the extruder are set as follows: the feeding section temperature is 168°C, the compression section temperature is 178°C, the metering section temperature is 188°C, and the die head temperature is 198°C.
[0084] S5. Preparation of an outer protective layer: The components of the outer protective layer of the fire hose are uniformly mixed according to weight proportions, and then stirred at 165° C. to obtain a colloid, which is then extruded onto the flame retardant layer to obtain the outer protective layer.
[0085] S6. Heat treatment: The prepared fire hose is heat treated at 83°C for 2h to release the internal stress, and then the mold is taken out to complete the preparation of the flame-retardant high-strength fire hose.
[0086] Example 3
[0087] A flame-retardant and high-strength fire hose, which comprises an outer protective layer, a flame-retardant layer, a braided layer, a reinforcement layer and an inner lining layer from the outside to the inside;
[0088] The flame retardant layer is composed of the following raw materials in parts by weight: 6 parts of surface modified magnesium hydroxide microtube coated flame retardant, 12 parts of thermoplastic elastomer, 7 parts of polypropylene, 16 parts of polyethylene, 1.4 parts of Irganox 1010 antioxidant, 4 parts of ethylene-vinyl acetate copolymer, 1.4 parts of nano-montmorillonite and 0.9 parts of zinc stearate;
[0089] The surface-modified magnesium hydroxide microtube-coated flame retardant is prepared by surface modification of magnesium hydroxide microtube-coated ammonium polyphosphate and maleic anhydride grafted polypropylene.
[0090] The reinforcing layer is composed of the following raw materials in parts by weight: 8 parts of surface modified beaded silicon carbide nanowires, 39 parts of polyvinyl chloride resin, 16 parts of ethylene-vinyl acetate copolymer, 4 parts of dioctyl adipate, 2.2 parts of castor oil, 1.5 parts of stearic acid, and 0.9 parts of zinc stearate.
[0091] The surface-modified linked beaded silicon carbide nanowires are prepared by surface-modifying the linked beaded silicon carbide nanowires with 3-methacryloxypropyltrimethoxysilane.
[0092] The preparation method of the surface modified magnesium hydroxide microtube coated organic flame retardant is as follows: by weight, 8 parts of magnesium chloride are dissolved in 1000 parts of deionized water, stirred until completely dissolved, 2 mol / L NaOH aqueous solution is slowly added dropwise until the pH reaches 11, the mixture is transferred to a hydrothermal reactor, reacted at 150°C for 13 hours, cooled to room temperature, centrifuged, washed with deionized water and ethanol 3 times, and finally vacuum dried at 61°C for 13 hours to obtain magnesium hydroxide microtubes. 6 parts of ammonium polyphosphate, 1.6 parts of sodium dodecyl sulfate and 50 parts of deionized water are mixed evenly, the solution is adjusted to pH 5 with 2% dilute hydrochloric acid, and then 7 parts of magnesium hydroxide microtubes are added, ultrasonically treated for 21 minutes, and then the mixture is transferred to a hydrothermal reactor, reacted at 112°C for 8 hours, cooled to room temperature, centrifuged to obtain solid powder, washed with deionized water 3 times, and finally vacuum dried at 60°C for 15 hours to obtain magnesium hydroxide microtube coated flame retardant. After 4 parts of maleic anhydride grafted polypropylene and 100 parts of butyl acetate are evenly mixed, 8 parts of magnesium hydroxide microtube coated flame retardant are added thereto and stirred for 8 minutes, and then filtered to remove solid powder, which is then completely dried in a vacuum drying oven at room temperature.
[0093] The preparation method of surface-modified beaded silicon carbide nanowires is as follows: 32 parts of polycarbosilane, 2 parts of ferrocene and 100 parts of xylene are mixed evenly by weight, and then placed in a vacuum drying oven, dried for 19 hours to obtain a solid precursor, and then the solid precursor is ground into powder and placed in a ceramic ark, placed in an atmosphere tube furnace, heated to 1320°C under an argon atmosphere, kept warm for 3 hours, and then cooled to room temperature to obtain beaded silicon carbide nanowires. 42 parts of beaded silicon carbide nanowires and 500 parts of anhydrous ethanol are added to a beaker, and then 6 parts of 3-methacryloxypropyltrimethoxysilane are added, followed by stirring at room temperature for 78 minutes. After stirring, the solid powder is collected by filtration, and dried completely in a vacuum drying oven at room temperature to obtain surface-modified beaded silicon carbide nanowires.
[0094] The outer protective layer is prepared from the following components in parts by weight: 21 parts of stainless steel powder, 7 parts of aluminum oxide powder, 6 parts of basalt fiber roving, 48 parts of ethylene-vinyl acetate copolymer, 15 parts of polypropylene and 4 parts of fluorescent powder.
[0095] The thickness of the outer protective layer is 1.0 mm; the thickness of the flame retardant layer is 1.8 mm; the thickness of the braided layer is 1.3 mm; the thickness of the reinforcement layer is 2.2 mm; and the thickness of the inner lining layer is 1.6 mm.
[0096] This embodiment also provides a method for preparing a highly wear-resistant UV matte coating, comprising the following steps:
[0097] S1. Preparation of inner lining layer: heating EPDM rubber to 188° C. to obtain a colloid, feeding it into an extruder, extruding it on a cylindrical mold, and obtaining a cylindrical inner lining layer after cooling.
[0098] S2. Preparation of a reinforcing layer: The components for preparing the reinforcing layer are mixed uniformly according to their weight proportions and then added into a furnace for smelting at a smelting temperature of 204° C. The smelted colloid is sent to a twin-screw extruder for extrusion. After cooling, a reinforcing layer is obtained outside the lining layer. The twin-screw extruder has a screw L / D ratio of 36:1 and a rotation speed of 130 rpm.
[0099] S3. Prepare the braided layer: apply adhesive on the reinforcement layer, and use nylon wire and fine steel wire to interlace and pull to weave the warp and weft to form a braided layer. The braiding density of the braided layer is 18 strands / inch, and the braiding angle is 53°.
[0100] S4, preparation of flame retardant layer: the components for preparing the flame retardant layer are mixed uniformly according to weight proportions and added into a furnace for melting at a melting temperature of 204°C, and then extruded through an extruder to form a flame retardant layer wrapped around the strong braided layer. The parameters of the extruder are set as follows: the feeding section temperature is 171°C, the compression section temperature is 181°C, the metering section temperature is 191°C, and the die head temperature is 201°C.
[0101] S5. Preparation of an outer protective layer: The components of the outer protective layer of the fire hose are uniformly mixed according to weight proportions, and then stirred at 180° C. to obtain a colloid, which is then extruded onto the flame retardant layer to obtain the outer protective layer.
[0102] S6. Heat treatment: The prepared fire hose is heat treated at 86° C. for 3 hours to release internal stress, and then the mold is taken out to complete the preparation of the flame-retardant high-strength fire hose.
[0103] Example 4
[0104] A flame-retardant and high-strength fire hose, which comprises an outer protective layer, a flame-retardant layer, a braided layer, a reinforcement layer and an inner lining layer from the outside to the inside;
[0105] The flame retardant layer is composed of the following raw materials in parts by weight: 7 parts of surface modified magnesium hydroxide microtube coated flame retardant, 15 parts of thermoplastic elastomer, 8 parts of polypropylene, 18 parts of polyethylene, 1.6 parts of Irganox 1010 antioxidant, 5 parts of ethylene-vinyl acetate copolymer, 2 parts of nano-montmorillonite and 1.2 parts of zinc stearate;
[0106] The surface-modified magnesium hydroxide microtube-coated flame retardant is prepared by surface modification of magnesium hydroxide microtube-coated ammonium polyphosphate and maleic anhydride grafted polypropylene.
[0107] The reinforcing layer is composed of the following raw materials in parts by weight: 10 parts of surface modified beaded silicon carbide nanowires, 45 parts of polyvinyl chloride resin, 18 parts of ethylene-vinyl acetate copolymer, 5 parts of dioctyl adipate, 3.0 parts of castor oil, 1.8 parts of stearic acid, and 1.2 parts of zinc stearate.
[0108] The surface-modified linked beaded silicon carbide nanowires are prepared by surface-modifying the linked beaded silicon carbide nanowires with 3-methacryloxypropyltrimethoxysilane.
[0109] The preparation method of the surface modified magnesium hydroxide microtube coated organic flame retardant is as follows: by weight, 10 parts of magnesium chloride are dissolved in 1000 parts of deionized water, stirred until completely dissolved, 2 mol / L NaOH aqueous solution is slowly added dropwise until the pH reaches 11, the mixture is transferred to a hydrothermal reactor, reacted at 120°C for 15 hours, cooled to room temperature, centrifuged, washed with deionized water and ethanol 3 times, and finally vacuum dried at 65°C for 15 hours to obtain magnesium hydroxide microtubes. 8 parts of ammonium polyphosphate, 2.0 parts of sodium dodecyl sulfate and 50 parts of deionized water are mixed evenly, the solution is adjusted to pH 5 with 2% dilute hydrochloric acid, and then 9 parts of magnesium hydroxide microtubes are added, ultrasonically treated for 25 minutes, and then the mixture is transferred to a hydrothermal reactor, reacted at 120°C for 10 hours, cooled to room temperature, centrifuged to obtain solid powder, washed with deionized water 3 times, and finally vacuum dried at 60°C for 18 hours to obtain magnesium hydroxide microtube coated flame retardant. After 5 parts of maleic anhydride grafted polypropylene and 100 parts of butyl acetate are evenly mixed, 10 parts of magnesium hydroxide microtube coated flame retardant are added thereto and stirred for 10 minutes, and then filtered to remove the solid powder, which is then completely dried in a vacuum drying oven at room temperature.
[0110] The preparation method of surface-modified beaded silicon carbide nanowires is as follows: 40 parts of polycarbosilane, 3 parts of ferrocene and 100 parts of xylene are mixed evenly by weight, and then placed in a vacuum drying oven, dried for 24 hours to obtain a solid precursor, and then the solid precursor is ground into powder and placed in a ceramic ark, placed in an atmosphere tube furnace, heated to 1400°C under an argon atmosphere, kept warm for 4 hours, and then cooled to room temperature to obtain beaded silicon carbide nanowires. 50 parts of beaded silicon carbide nanowires and 500 parts of anhydrous ethanol are added to a beaker, and then 8 parts of 3-methacryloxypropyltrimethoxysilane are added, followed by stirring at room temperature for 90 minutes. After stirring, the solid powder is collected by filtration, and dried completely in a vacuum drying oven at room temperature to obtain surface-modified beaded silicon carbide nanowires.
[0111] The outer protective layer is prepared from the following components in parts by weight: 25 parts of stainless steel powder, 9 parts of aluminum oxide powder, 8 parts of basalt fiber roving, 60 parts of ethylene-vinyl acetate copolymer, 18 parts of polypropylene and 5 parts of fluorescent powder.
[0112] The thickness of the outer protective layer is 1.2 mm; the thickness of the flame retardant layer is 2.0 mm; the thickness of the braided layer is 1.5 mm; the thickness of the reinforcement layer is 2.5 mm; and the thickness of the inner lining layer is 1.8 mm.
[0113] This embodiment also provides a method for preparing a highly wear-resistant UV matte coating, comprising the following steps:
[0114] S1. Preparation of inner lining layer: heating EPDM rubber to 200° C. to obtain a colloid, feeding it into an extruder, extruding it on a cylindrical mold, and obtaining a cylindrical inner lining layer after cooling.
[0115] S2. Preparation of a reinforcing layer: The components for preparing the reinforcing layer are mixed uniformly according to their weight proportions and then added into a furnace for smelting at a smelting temperature of 220° C. The smelted colloid is sent to a twin-screw extruder for extrusion. After cooling, a reinforcing layer is obtained outside the lining layer. The twin-screw extruder has a screw L / D ratio of 36:1 and a rotation speed of 150 rpm.
[0116] S3. Prepare the braided layer: apply adhesive on the reinforcement layer, and use nylon wire and fine steel wire to interlace and pull to weave the warp and weft to form a braided layer. The braiding density of the braided layer is 20 strands / inch, and the braiding angle is 55°.
[0117] S4, preparation of flame retardant layer: the components for preparing the flame retardant layer are mixed uniformly according to weight proportions and added into a furnace for melting at a melting temperature of 220°C, and then extruded through an extruder to form a flame retardant layer wrapped around the strong braided layer. The parameters of the extruder are set as follows: the feeding section temperature is 175°C, the compression section temperature is 185°C, the metering section temperature is 195°C, and the die head temperature is 205°C.
[0118] S5. Preparation of an outer protective layer: The components of the outer protective layer of the fire hose are uniformly mixed according to weight proportions, and then stirred at 200° C. to obtain a colloid, which is then extruded onto the flame retardant layer to obtain the outer protective layer.
[0119] S6. Heat treatment: The prepared fire hose is heat treated at 90° C. for 3 hours to release internal stress, and then the mold is taken out to complete the preparation of the flame-retardant high-strength fire hose.
[0120] Example 5
[0121] It is basically the same as Example 1, except that the amount of the surface-modified magnesium hydroxide microtube-coated flame retardant added in the preparation of the flame retardant layer is 7 parts.
[0122] Example 6
[0123] It is basically the same as Example 1, except that the number of surface-modified beaded silicon carbide nanowires added in the preparation of the strong layer is 10 parts.
[0124] Comparative Example 1
[0125] The method is basically the same as Example 1, except that the flame retardant coated magnesium hydroxide microtubes used to prepare the flame retardant layer is not subjected to surface modification treatment.
[0126] Comparative Example 2
[0127] It is basically the same as Example 1, except that the surface modified magnesium hydroxide microtubes used to prepare the flame retardant layer are not coated with flame retardant, but the surface modified magnesium hydroxide microtubes used replace the surface modified magnesium hydroxide microtubes coated with flame retardant.
[0128] The preparation method of surface-modified magnesium hydroxide microtubes is as follows: The preparation method of surface-modified magnesium hydroxide microtubes coated with organic flame retardant is as follows: by weight, 5 parts of magnesium chloride are dissolved in 1000 parts of deionized water, stirred until completely dissolved, 2 mol / L NaOH aqueous solution is slowly added dropwise until the pH reaches 10, the mixture is transferred to a hydrothermal reactor, reacted at 170°C for 10 hours, cooled to room temperature, centrifuged, washed with deionized water and ethanol for 3 times, and finally vacuum dried at 55°C for 10 hours to obtain magnesium hydroxide microtubes. After 2 parts of maleic anhydride grafted polypropylene and 100 parts of butyl acetate are evenly mixed, 4 parts of magnesium hydroxide microtubes coated with flame retardant are added thereto and stirred for 5 minutes, then filtered to obtain solid powder, and then dried completely in a vacuum drying oven at room temperature.
[0129] Comparative Example 3
[0130] The method is basically the same as Example 1, except that the beaded silicon carbide nanowires added to the reinforcement layer have not been subjected to surface modification treatment.
[0131] Comparative Example 4
[0132] The method is basically the same as Example 1, except that an equal amount of surface-modified silicon carbide nanoparticles is added to the reinforcement layer.
[0133] The preparation method of surface-modified silicon carbide nanoparticles is as follows: by weight, 30 parts of connected silicon carbide nanoparticles and 500 parts of anhydrous ethanol are added to a beaker, and then 4 parts of 3-methacryloxypropyltrimethoxysilane are added, followed by stirring at room temperature for 60 minutes. After stirring, the solid powder is collected by filtration and dried completely in a vacuum drying oven at room temperature to obtain surface-modified silicon carbide nanoparticles.
[0134] Performance Testing:
[0135] Compression strength test: Refer to GB / T 5563-2013 "Hydrostatic test method for rubber and plastic hoses and hose assemblies" for testing. Detailed steps: Cut 2 meters of hose sample and install suitable connectors at both ends; connect the sample to the test equipment to ensure good sealing; slowly inject water and exhaust air, and evenly increase the pressure at a rate of 0.1MPa / s to the specified bursting pressure, and record the pressure value when leakage, bursting or any abnormality occurs.
[0136] Tensile strength test: refer to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". Detailed steps: Cut a standard dumbbell-shaped specimen from the hose, and the specimen should be free of bubbles or defects; mark the specified gauge length of 50mm on the specimen; load the specimen into the fixture of the tensile testing machine, ensuring that it is centered and does not slip; set the tensile speed to 500mm / min; start the testing machine and record the force-displacement curve throughout the process; record the maximum tensile force (breaking force) and elongation at break; calculate the tensile strength and elongation at break; repeat the test for at least 5 specimens and take the average value.
[0137] Flame retardant performance: The flame retardant performance test of the fire hose is carried out in accordance with the UL94 fire test standard. The test steps are as follows: First, cut a sample of standard size from the hose (usually 125±5mm in length and 13±0.5mm in width). Fix the sample vertically on the test stand, with the bottom about 300mm away from the burning paper pad. Use the specified burner and adjust the flame height to 20±1mm. Aim the bottom of the flame at the lower end of the sample and remove it after 10±0.5 seconds. Record the burning time of the sample, whether there are burning drips, and whether the burning paper is ignited. If the sample extinguishes itself within 30 seconds after the fire source is removed, and there are no burning drips to ignite the burning paper, repeat the ignition for 10 seconds. According to the burning behavior of the sample, it can be divided into V-0, V-1, V-2 and other levels, among which the V-0 level indicates the best flame retardant performance. This test method can effectively evaluate the safety and fire resistance of the fire hose in the case of fire, and ensure its reliability under extreme conditions.
[0138] The performances of the fire hoses of Examples 1 to 6 and Comparative Examples 1 to 4 are summarized in Table 2.
[0139] Table 2 Performance of fire hoses in Examples 1 to 6 and Comparative Examples 1 to 4
[0140]
[0141] The main difference between Comparative Example 1 and Example 1 is that the magnesium hydroxide microtubes coated with flame retardant are not subjected to surface modification treatment. As can be seen from Table 2, the bursting pressure, tensile strength and elongation of Example 1 are higher than those of Comparative Example 1, and the flame retardant performance reaches V-0 level, while Comparative Example 1 is only V-1 level. This is because the surface modification treatment can significantly improve the compatibility and dispersibility of magnesium hydroxide microtubes with the polymer matrix, thereby enhancing the overall mechanical properties and flame retardant effect of the water hose. Surface modification also helps to evenly distribute the flame retardant in the microtubes, thereby improving the flame retardant efficiency.
[0142] The main difference between Comparative Example 2 and Example 1 is that the flame retardant layer uses surface-modified magnesium hydroxide microtubes that are not coated with flame retardants. As can be seen from Table 2, although the mechanical properties of Comparative Example 2 are slightly lower than those of Example 1, the difference is not large. However, the flame retardant performance only reaches the V-1 level, which is significantly lower than the V-0 level of Example 1. This is because although the surface-modified magnesium hydroxide microtubes can provide a certain flame retardant effect and mechanical enhancement, they lack the flame retardant coated inside the microtubes, and cannot achieve a synergistic flame retardant effect, resulting in the overall flame retardant performance being inferior to that of Example 1.
[0143] The main difference between Comparative Example 3 and Example 1 is that the beaded silicon carbide nanowires in the reinforcement layer have not been surface modified. As can be seen from Table 2, the burst pressure, tensile strength and elongation of Comparative Example 3 are significantly lower than those of Example 1, while the flame retardant performance remains at the V-0 level. This is because the interface compatibility of the silicon carbide nanowires without surface modification and the polymer matrix is poor, resulting in a decrease in stress transfer efficiency, thereby affecting the overall mechanical properties of the hose. However, since the composition of the flame retardant layer has not changed, the flame retardant performance remains at a high level.
[0144] The main difference between Comparative Example 4 and Example 1 is that an equal amount of surface-modified silicon carbide nanoparticles is added to the reinforcement layer, rather than beaded nanowires. As can be seen from Table 2, the burst pressure, tensile strength and elongation of Comparative Example 4 are slightly lower than those of Example 1, and the flame retardant performance also reaches the V-0 level. This is because although the surface-modified silicon carbide nanoparticles can provide a certain reinforcement effect, their morphological structure is not as conducive to stress transmission and dispersion as the beaded nanowires. The beaded structure can form a more effective three-dimensional network in the polymer matrix, providing a better mechanical reinforcement effect without affecting the flame retardant performance.
[0145] The present invention proposes a high-performance fire hose, which has achieved comprehensive improvement in flame retardancy, mechanical properties and other aspects through innovative five-layer composite structure design and ingenious compounding of multiple functional materials, and has significant advantages over traditional fire hoses. In terms of flame retardancy, a composite material of surface-modified magnesium hydroxide microtubes coated with ammonium polyphosphate flame retardant is used to achieve a synergistic flame retardant effect; in terms of mechanical properties, surface-modified beaded silicon carbide nanowires are introduced and compounded with a polymer matrix, and nylon wire and fine steel wire are interlaced and woven, which greatly improves the strength and toughness of the hose; wear resistance is significantly improved by the reasonable compounding of stainless steel powder, aluminum oxide powder and basalt fiber roving. In addition, the present invention also takes into account the actual use needs, adopts hydrolysis-resistant and aging-resistant lining materials to improve water delivery efficiency, and adds fluorescent powder to the outer layer to realize night tracking function. The fire hose of the present invention has a tensile strength of greater than 22MPa and an elongation at break of greater than 310%, which is significantly better than the technical indicators of the tensile strength of the fire hose greater than 12MPa and the elongation at break greater than 280% in GB 6246-2011. Therefore, through the synergistic effect among various functional layers, the present invention has successfully developed a new type of high-performance fire hose that can maintain excellent comprehensive performance under extreme conditions, providing a reliable guarantee for improving fire extinguishing efficiency and firefighter safety, and showing broad application prospects.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A flame retardant high-strength fire hose, characterized in that: From outside to inside, they are outer protective layer, flame retardant layer, braided layer, reinforcement layer and inner lining layer; The flame retardant layer is composed of the following raw materials in parts by weight: 3-7 parts of surface modified magnesium hydroxide microtube coated flame retardant, 8-15 parts of thermoplastic elastomer, 5-8 parts of polypropylene, 12-18 parts of polyethylene, 1.0-1.6 parts of Irganox 1010 antioxidant, 2-5 parts of ethylene-vinyl acetate copolymer, 0.5-2 parts of nano-montmorillonite and 0.4-1.2 parts of zinc stearate; The surface-modified magnesium hydroxide microtube-coated flame retardant is prepared by surface-modifying the magnesium hydroxide microtube-coated flame retardant by maleic anhydride grafted polypropylene; The reinforcing layer is composed of the following raw materials in parts by weight: 5-10 parts of surface modified beaded silicon carbide nanowires, 30-45 parts of polyvinyl chloride resin, 12-18 parts of ethylene-vinyl acetate copolymer, 2-5 parts of dioctyl adipate, 1.0-3.0 parts of castor oil, 1.0-1.8 parts of stearic acid, and 0.6-1.2 parts of zinc stearate; The surface-modified linked beaded silicon carbide nanowires are prepared by surface-modifying linked beaded silicon carbide nanowires with 3-methacryloxypropyltrimethoxysilane. The preparation method of the magnesium hydroxide microtube coated flame retardant is as follows: by weight, 3-8 parts of ammonium polyphosphate, 1.0-2.0 parts of sodium dodecyl sulfate and 50 parts of deionized water are mixed evenly, the pH value of the solution is adjusted to 5 with 2% dilute hydrochloric acid, and then 4-9 parts of magnesium hydroxide microtubes are added, and ultrasonic treatment is performed for 15-25 minutes, and then the mixture is transferred to a hydrothermal reactor, reacted at 100-120° C. for 6-10 hours, cooled to room temperature, centrifuged to obtain solid powder, washed with deionized water for 3 times, and finally vacuum dried at 60° C. for 10-18 hours to obtain the magnesium hydroxide microtube coated flame retardant.
2. A flame retardant high-strength fire hose as claimed in claim 1, characterized in that: The preparation method of the surface modified magnesium hydroxide microtube coated flame retardant is as follows: after 2-5 parts of maleic anhydride grafted polypropylene and 100 parts of butyl acetate are evenly mixed by weight, 4-10 parts of magnesium hydroxide microtube coated flame retardant are added thereto and stirred for 5-10 minutes, and then filtered to obtain solid powder, which is then completely dried in a vacuum drying oven at room temperature.
3. A flame retardant high-strength fire hose as claimed in claim 1, characterized in that: The preparation method of the magnesium hydroxide microtube is as follows: by weight, 5-10 parts of magnesium chloride are dissolved in 1000 parts of deionized water, stirred until completely dissolved, 2 mol / L NaOH aqueous solution is slowly added dropwise until the pH reaches 10-11, the mixture is transferred to a hydrothermal reactor, reacted at 170-120° C. for 10-15 hours, cooled to room temperature, centrifuged, washed with deionized water and ethanol for 3 times respectively, and finally vacuum dried at 55-65° C. for 10-15 hours to obtain the magnesium hydroxide microtube.
4. A flame retardant high-strength fire hose as claimed in claim 1, characterized in that: The preparation method of the surface-modified beaded silicon carbide nanowires is as follows: by weight, 30 to 50 parts of beaded silicon carbide nanowires and 500 parts of anhydrous ethanol are added to a beaker, and then 4 to 8 parts of 3-methacryloxypropyltrimethoxysilane are added, followed by stirring at room temperature for 60 to 90 minutes. After the stirring is completed, the solid powder is collected by filtering, and the surface-modified beaded silicon carbide nanowires are obtained after being completely dried in a vacuum drying oven at room temperature.
5. A flame retardant high-strength fire hose as claimed in claim 1 or 4, characterized in that: The preparation method of the beaded silicon carbide nanowires is as follows: after uniformly mixing 20 to 40 parts of polycarbosilane, 1 to 3 parts of ferrocene and 100 parts of xylene, the mixture is placed in a vacuum drying oven and dried for 12 to 24 hours to obtain a solid precursor, and then the solid precursor is ground into powder and placed in a ceramic ark, which is then placed in an atmosphere tube furnace, heated to 1200 to 1400° C. under an argon atmosphere, kept warm for 2 to 4 hours, and then cooled to room temperature to obtain the beaded silicon carbide nanowires.
6. The flame retardant high-strength fire hose according to claim 1, characterized in that: The outer protective layer is prepared from the following components in parts by weight: 15 to 25 parts of stainless steel powder, 4 to 9 parts of aluminum oxide powder, 3 to 8 parts of basalt fiber roving, 30 to 60 parts of ethylene-vinyl acetate copolymer, 10 to 18 parts of polypropylene and 2 to 5 parts of fluorescent powder.
7. The flame retardant high-strength fire hose according to claim 1, characterized in that: The thickness of the outer protective layer is 0.8-1.2 mm; the thickness of the flame retardant layer is 1.5-2.0 mm; the thickness of the braided layer is 1.0-1.5 mm; the thickness of the reinforcement layer is 1.8-2.5 mm; and the thickness of the lining layer is 1.2-1.8 mm.
8. A method for preparing a flame-retardant high-strength fire hose according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Preparation of inner lining layer: heating EPDM rubber to 170-200°C to obtain a colloid, feeding it into an extruder, extruding it on a cylindrical mold, and obtaining a cylindrical inner lining layer after cooling; S2. Preparation of a reinforcing layer: The components for preparing the reinforcing layer are mixed uniformly according to weight proportions and then added into a furnace for smelting at a smelting temperature of 180-220° C. The smelted colloid is sent into a twin-screw extruder for extrusion, and after cooling, a reinforcing layer is obtained outside the inner lining layer; S3, preparing the braided layer: applying an adhesive on the reinforcing layer, and using nylon thread and fine steel wire to interlace and pull to weave the warp and weft to form a braided layer; S4, preparing a flame retardant layer: mixing the components for preparing the flame retardant layer uniformly according to weight proportions and adding them into a furnace for melting at a melting temperature of 180-220° C., and then extruding them through an extruder to form a flame retardant layer wrapping the braided layer; S5. preparing an outer protective layer: the components of the outer protective layer of the fire hose are uniformly mixed according to weight proportions, and then stirred at 150-200° C. to obtain a colloid, which is then extruded onto the flame retardant layer to obtain an outer protective layer; S6. Heat treatment: The prepared fire hose is heat treated at 80-90°C for 2-3h to release the internal stress, and then the mold is taken out to complete the preparation of the flame-retardant high-strength fire hose.
9. The method for preparing a flame-retardant high-strength fire hose according to claim 8, characterized in that: The twin-screw extruder in step S2 has a screw L / D ratio of 36:1 and a rotation speed of 100-150 rpm; The braiding density of the braided layer in step S3 is 16-20 strands / inch, and the braiding angle is 50-55°; The parameters of the extruder in step S4 are set as follows: the temperature of the feed section is 165-175°C; the temperature of the compression section is 175-185°C; the temperature of the metering section is 185-195°C; and the temperature of the die head is 195-205°C.
Citation Information
Patent Citations
Inflaming retarding fire hose
CN103438299A
High-strength fire hose
CN111140708A
Preparation method of magnesium hydroxide nanotube
CN114655971A
High-strength wear-resistant fire hose and preparation method thereof
CN114776898A